The influence of research self-efficacy and learning engagement on Ed.D students’ academic achievement - Haifei Miao; Rong Guo; Ming Li (Frontiers in Psychology)
IntroductionThe doctor of education (Ed.D) degree plays a crucial role in developing highly specialized professionals in the field of education. Previous researches have shown that research self-efficacy is a positive psychological factor that enhances students’ academic performance. However, there is limited research specifically addressing how to improve the academic achievement of Ed.D students in higher education.MethodsGrounded in social cognitive theory, this study aims to examine the predictive power of research self-efficacy and the mediating role of student engagement in the academic achievement of Ed.D students. A total of 310 participants were included in this study. Pearson correlation coefficients were used to explore the relationships between research self-efficacy, learning engagement, and academic achievement. Mediation analysis was conducted to assess the indirect effect of student engagement on the relationship between research self-efficacy and academic achievement.ResultsThe findings revealed significant and positive correlations among research self-efficacy, learning engagement, and academic achievement. Research self-efficacy was found to directly predict academic achievement and also to indirectly influence it through the mediating effect of student engagement. Learning engagement refers to the degree of effort, persistence, concentration, problem-solving strategies, and affective connection that a student demonstrates during learning activities, encompassing cognitive, emotional, and behavioral dimensions. That is, the higher the Ed.D students’ research self-efficacy, the more they invest in cognitive, emotional and behavioral engagement, actively participating in learning and research activities, which in turn enhances their academic achievement.DiscussionThese results provide valuable insights into the mechanisms by which research self-efficacy influences academic achievement in Ed.D students, highlighting the importance of learning engagement. The study’s findings have implications for designing interventions aimed at enhancing Ed.D students’ academic success.